संस्कृत साहित्ये नैपालमिथिलाक्षेत्रस्य योगदानम् [Contribution of Nepali Mithila Region in Sanskrit Literature] - पाण्डेय Pandey गणेश Ganesh (Haimaprabha, 2021)
सूर्यवंशीयराज्ञो निमेः शरीरमन्थनाज्जातेन मिथिनाम्ना राज्ञा प्रवर्तितत्वात् तदीया राजधानी मिथिलेति प्रसिद्धिमुपगता । मिथिलायाः सीमासङ्कोचविस्तारयोर्जातेऽपि प्रवृmताध्ययने नेपालस्य साम्प्रतिकः द्विसङ्ख्यकः प्रदेशः मिथिलाक्षेत्रत्वेन गृहीतः । मिथिलाराज्यस्य सीमायाः परिवर्तने दृष्टेऽपि मिथिलासंस्वृते राजधानी जनकपुरं वर्तते । मिथिलायां वैदिककाले विश्वामित्रप्रभृतयो ऋषयो दृश्यन्ते । तेषु महर्षिर्याज्ञवल्क्यः सर्वाधिक्येन प्रदीप्तं मिथिलायाः प्रोज्ज्वलं रत्नं वर्तते । अर्वाचीनेषु कविषु वंशमणिशर्मा हरिकेलिमहाकाव्यमाध्यमेन सर्वोत्वृष्टं स्थानं लभते । मिथिलायां स्फुटरूपेण संस्वृmतकवितारचनायाः परम्परा सम्प्रत्यपि जीविता वर्तते । [This research confirms that the naming of the Mithila region was initiated by a king named Mithi, who was born by churning the body of Suryavanshi king Nimi. Although the border of Mithila has been constricting and widening over time, in this study, the current state number two of Nepal has been taken as Mithila region. Janakpur remained the capital of Mithilaculture even when the borders of Mithila state changed. Vishwamitra and other sages have been seen in Mithila during the Vedic period. Among them, MaharshiYajnavalkya is the brightest gem. In the modern age, it has been confirmed that Vanshamani Sharma has reached the best place through the epic Harikeli. This research has confirmed that the tradition of composing Sanskrit poetry in Mithila is still alive today.]